Experimental study on physical properties of modified jatropha oilbased nanofluids for machining purposes - Norfazillah, Talib; Ainaa Mardhiah, Sabri; Haslina, Abdullah; Amiril Sahab, Abdul Sani (Elsevier Ltd, 2022)
Vegetable-based crude jatropha oil (CJO) was utilized to substitute petroleum-based oil as a metalworking fluid. The usage of petroleum-oil based as a metalworking fluid causes a major concern to the environment and health issues. Besides that, it has a high quantity of free fatty acid (FFA), which causes physical deterioration. This study aims to physically test the new formulation oil-based on modified jatropha nanofluids as the metalworking fluid for machining purposes. To create modified jatropha oil (MJO), CJO was chemically modified through the esterification and transesterification process. MJO was combined with nanoparticles which are activated carbon (AC) at the concentration of 0.01 wt%, 0.025 wt% and 0.05 wt% to create the nanofluids. The properties of MJO nanofluids were tested using ASTM standards for viscosity and acid value and were compared with the synthetic ester (SE). All of the results indicate that the physical qualities improved during the storage period. MJOa3 (MJO + 0.05 wt% AC), it may be inferred, has potential as a long-term metalworking fluid for the machining process. Based on the experiment result, for kinematic viscosity, MJOa3 shows better results during the period from day 1 to day 7 compared to non-additive MJO. MJOa3 recorded the highest viscosity index (184). In addition, MJOs have the lowest acid value of 0.4 to 0.48 mg NaOH/g. In conclusion, the presence of AC helps MJO to improve their properties and MJOa3 shows excellent lubricant properties from all the samples.